Angiotensin-(1–7) attenuates SARS-CoV2 spike protein-induced interleukin-6 and interleukin-8 production in alveolar epithelial cells through activation of Mas receptor - Yi-Luen Shen; Yi-An Hsieh; Po-Wei Hu; Po-Chun Lo; Yi-Han Hsiao; Hsin-Kuo Ko; Fang-Chi Lin; Chien-Wen Huang; Kang-Cheng Su; Diahn-Warng Perng (Journal of Microbiology, Immunology and Infection, 2023)
Background: SARS-CoV-2 spike proteins (SP) can bind to the human angiotensin-converting enzyme 2 (ACE2) in human pulmonary alveolar epithelial cells (HPAEpiC) and trigger an inflammatory process. Angiotensin-(1–7) may have an anti-inflammatory effect through activation of Mas receptor. This study aims to investigate whether SARS-CoV-2 SP can induce inflammation through ACE2 in the alveolar epithelial cells which can be modulated through angiotensin-(1–7)/Mas receptor axis. Methods: HPAEpiC were treated with SARS-CoV-2 SP in the presence or absence of ACE2 antagonist-dalbavancin and Mas receptor agonist-angiotensin-(1–7). Proinflammatory cytokine production (IL-6 and IL-8) were measured at mRNA and protein levels. MAP kinase phosphorylation and transcription factor activation was determined by Western Blot. Mas receptor was blocked by either antagonist (A779) or knockdown (specific SiRNA). Experiments were replicated using A549 cells. Findings: SARS-CoV-2 SP (5 μg/mL) significantly induced MAP kinase (ERK1/2) phosphorylation, downstream transcription factor (activator protein-1, AP-1) activation and cytokine production (IL-6 and IL-8) at both mRNA and protein levels. Pretreatment with dalbavancin (10 μg/mL), or angiotensin-(1–7) (10 μM) significantly reduced ERK1/2 phosphorylation, AP-1 activation, and cytokine production. However, these angiotensin-(1–7)-related protective effects were significantly abolished by blocking Mas receptor with either antagonist (A799,10 μM) or SiRNA knockdown. Interpretation: SARS-CoV-2 SP can induce proinflammatory cytokine production, which can be inhibited by either ACE2 antagonist or Mas receptor agonist-angiotensin-(1–7). Angiotensin-(1–7)-related protective effect on cytokine reduction can be abolished by blocking Mas receptor. Our findings suggest that ACE2/angiotensin-(1–7)/Mas axis may serve as a therapeutic target to control inflammatory response triggered by SARS-CoV-2 SP.